Pareto-efficient climate agreements - Geir B. Asheim; Bjart Holtsmark (Statistics Norway, Research Department, 2007)
Recent contributions show that climate agreements with broad participation can be implemented as weakly renegotiation-proof equilibria in simple models of greenhouse gas abatement where each country has a binary choice between cooperating (i.e., abate emissions) or defecting (no abatement). Here we show that this result carries over to a model where countries have a continuum of emission choices. Indeed, a Pareto-efficient climate agreement can always be implemented as a weakly renegotiation-proof equilibrium, for a sufficiently high discount factor. This means that one need not trade-off a "narrow but deep" treaty with a "broad but shallow" treaty.
Keywords: C72; F53; Q54; 330; Climate; non-cooperative game-theory; repeated games; weakly renegotiation-proof agreements